DIFFERENT PERCEPTIONS OF ETHICAL PRACTICE IN EARNINGS MANAGEMENT ACCOUNTING STUDENTS IN THE GENDER PERSPECTIVE IN YOGYAKARTA - Anggoroseto, Jati; Setyawan, Dr. Aris Budi (Accounting, 2010)
Earnings management is an act of managers to increase (decrease) current reported earnings on a unit where the manager is responsible, without leading to an increase (decrease) in long-term economic profitability of the unit. Earnings management or earnings management is one area in which controversial as an acceptable attitude (acceptable) or not acceptable (unacceptable). This study replicates previous research Clickeman (2000) and Nurmala (2007). This study aims to find out about the views of ethical perceptions between male accounting students and women against the practice of earnings management. Testing research methods from Clickeman previous research (2000) is to spread the 13 questionnaires relating to the practice of earnings management to look average. In addition, researchers also tested the re-study with test reliability, test validity, test for normality and hypothesis testing. The results of this study can be seen that there is no ethical difference between accounting students male and female accounting students about the practice of earnings management. But it can be concluded from these studies that women are more looking at the practice of earnings management is something that is more unethical than men. Keywords: earnings management.